2007
DOI: 10.1007/s11104-006-9122-3
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic N2 fixation by soybean in organic and conventional cropping systems estimated by 15N dilution and 15N natural abundance

Abstract: Nitrogen (N) is often the most limiting nutrient in organic cropping systems. N 2 fixing crops present an important option to improve N supply and to maintain soil fertility. In a field experiment, we investigated whether the lower N fertilization level and higher soil microbial activity in organic than conventional systems affected symbiotic N 2 fixation by soybean (Glycine max, var. Maple Arrow) growing in 2004 in plots that were since 1978 under the following systems: biodynamic (DYN); bio-organic (ORG); co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 35 publications
9
47
0
3
Order By: Relevance
“…Although in the present study 42% to 65% of soybean N was obtained from BNF, this could not turn then balance into a positive one. Similar soybean N balances have been reported for Argentina [34] and Switzerland [35]. In fact, in their review of BNF studies that had been conducted between 1966 and 2006, [8] observed that the amount of fixed N in soybean (a grain legume as opposed to non-grain legumes or legumes where the grain is usually not harvested) was, in most cases, insufficient to replace all the N removed in harvested seed.…”
Section: Nitrogen Fixed and N Balancessupporting
confidence: 58%
“…Although in the present study 42% to 65% of soybean N was obtained from BNF, this could not turn then balance into a positive one. Similar soybean N balances have been reported for Argentina [34] and Switzerland [35]. In fact, in their review of BNF studies that had been conducted between 1966 and 2006, [8] observed that the amount of fixed N in soybean (a grain legume as opposed to non-grain legumes or legumes where the grain is usually not harvested) was, in most cases, insufficient to replace all the N removed in harvested seed.…”
Section: Nitrogen Fixed and N Balancessupporting
confidence: 58%
“…To calculate the B value, we used was the most negative value detected, which in soybean was -1.43‰, and in red clover was -1.84‰. This is similar to earlier reported values for soybean (-1.2‰) (Oberson et al, 2007).…”
Section: Plant Measurementssupporting
confidence: 86%
“…An on-farm study that evaluated a gradient of management practices that varied in reliance on organic N amendments found evidence for downregulation of BNF in fields with enhanced soil inorganic N and other altered edaphic properties (Schipanski and Drinkwater 2012). However, a field experiment using 15 N natural abundance and dilution techniques demonstrated the opposite effect: elevated soybean BNF rates under organic and compost-based management were found with enhanced soil organic N pools, relative to N-fertilizer management (Oberson et al, 2007). Neither of these studies were performed over multiple years, and seasonal effects in rain-fed production systems are expected to be important as soil moisture has been shown to strongly regulate BNF in many legumes (Purcell et al, 2004).…”
Section: Compost Legacy Down-regulates Biological Nitrogen Fixation Imentioning
confidence: 99%
See 2 more Smart Citations